Simulation of Central Porosity and Hot Crack Formation in 14 t Flat Ingot by Mold Removal Controlled Cooling - Wu Gang, Xu Changjun, Feng Xulong, Zhai Haodong, Xu Jichen, Hu Hanting (Teshugang)
Taking 14 t flat ingot as the research object， a new method of mold removal controlled cooling was adopted. This method completely eliminates the effect of the air gap in the solidification process of the ingot， and applies cooling to the lower part of the ingot to promote the sequence solidification of ingot from bottom to top， thus improving the solidification quality of the ingot. The heat transfer solidification process of the cooling steel ingot controlled by mold removal was simulated through the simulation software combined with the industrial test of solidification process of 14 t H13 on site， and the influence of different cooling intensities on heat transfer solidification， Niyama distribution and thermal stress of steel ingot was analyzed. The results show that the temperature gradient of the lower part of the ingot is increased by mold removal and controlled cooling， the solidification front changes from U-shape to V-shape， the angle of solidification front is increased， the feeding channel between the riser and the solidification front is widened， and the feeding of the riser to the lower part is promoted. With the increase of cooling intensity， the central loose area decreased by 2.03%， the central loose length decreased by 68.53%， and concentrated in the riser area. At the same time， the thermal stress inside the ingot also increases， and the proposed cracking coefficient is used to predict the risk of cracking when the controlled cooling intensity reaches 1 200（W·m-2·K-1）.